Investigation of Influential Parameters in Deep Oxidative Desulfurization of Dibenzothiophene with Hydrogen Peroxide and Formic Acid. (12th June 2013) - Haghighat Mamaghani, Alireza; Fatemi, Shohreh; Asgari, Mehrdad
Abstract : An effective oxidative system consisting of hydrogen peroxide, formic acid, and sulfuric acid followed by an extractive stage were implemented to remove dibenzothiophene in the simulated fuel oil. The results revealed such a great performance in the case of H2 O2 in the presence of formic and sulfuric acids that led to the removal of sulfur compounds. Sulfuric acid was employed to increase the acidity of media as well as catalytic activity together with formic acid. The oxidation reaction was followed by a liquid-liquid extraction stage using acetonitrile as a polar solvent to remove produced sulfones from the model fuel. The impact of operating parameters including the molar ratio of formic acid to sulfur (n F / n S ), hydrogen peroxide to sulfur (n O / n S ), and the time of reaction was investigated using Box-Behnken experimental design for oxidation of the model fuel. A significant quadratic model was introduced for the sulfur removal as a function of effective parameters by the statistic analysis.